Hepatoenteric shunts with diverticular loops in the treatment of non-tumor biliary conditions - Praderi, Raúl; Delgado, Bolívar; Ormaechea, Carlos (Cirugía del Uruguay, 1972)
This is a report of the results obtained in the treatment of 14 cases of non-tumoral disease of the biliary tract with bilio-digestive anastomosis on diverticular loops. Eleven cases of main biliary tract lesions after cholecystectomie, s were treated: 1 delayed postoperatory choledoco-duodenal fistula, 1 post-gastrectomy stenosis and one oriental-type intrahepatic lithiasis. In two cases termino terminal hepatoduodenostomies were performe.d on the duodenal stump after gastrectomies Billroth II. In 11 cases termino lateral hepatojejunostomies were performed. In one (intrahepatic lithiasis) two hepatojejunostomies were performed on the same loop, using the common and left hepatic duct. In ali cases anastomosis were calibrated by means of transanastomotic tu bes: Through the hepatic duct in two cases in which a healthy fragment thereof was left; in Witzel's manner in the case of double anastomosis; with transhepatic tubes in the remaining patients. The latter technique has been perfected by the authors and is the one. which offers least risk. The 14 patients did well, although only three underwent the first reoperation by the authors. The majority of them had already been reoperated by other surgeons previoosly, once, twice, three or even four times. One patient had suffered from stenosis of the common bile duct for 20 years and had biliary cirrhosis with portal hoypertension, so additional spleno-renal anastomosis was performed.